The Sensorium: A Multimodal Neurofeedback Environment. (5th October 2010) - Hinterberger, Thilo
Abstract : The Sensorium is a neurofeedback environment that allows people to experience signals from their nonperceptible body processes visually and auditorily. Various (neuro-)physiological rhythms and frequencies are projected simultaneously as soundscapes and "lightscapes" into the environment. A wireless physiological amplifier device sends signals such as EEG and ECG to a computer for real-time processing using the modified brain-computer interface software "Thought Translation Device" (TTD). The TTD performs signal filtering, parametric orchestral sonification, and light control. In a pilot study, 20 participants have been exposed to their ongoing brain and heart signals while sitting inside the Sensorium, a small room equipped with a speaker and lighting system. Almost all of them reported an increase in contentment, relaxation, happiness, and inner harmony. They also reported a widening in their body consciousness. In future, therapeutic paradigms will be developed and the treatment effects on people with psychosomatic diseases will be evaluated.